2006 IEEE International Symposium on MicroNanoMechanical and Human Science 2006
DOI: 10.1109/mhs.2006.320292
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of actin sliding over myosin thick filaments in vitro

Abstract: It is customarily thought that myosin motors act as independent force-generators in both isotonic unloaded shortening as well as isometric contraction of muscle. We tested this assumption regarding unloaded shortening, by analyzing the fluctuation of the actin sliding movement over long native thick filaments from molluscan smooth muscle in vitro. This analysis is based on the prediction that the effective diffusion coefficient of actin, a measure of the fluctuation, is proportional to the inverse of the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Their orientation is, however, important for proper interpretation of such experiments [Sekimoto and Tawada, 1995;Imafuku et al, 1996]. Long thick filaments of bivalve muscles were used to overcome this problem, and it was concluded that some cooperative coordination exists between many motors on thick filaments in the actomyosin system [Noda et al, 2005]. Similarly, the present experimental system can be used for the kinesinmicrotubule motility system.…”
Section: Discussion Catchin Filaments Are Useful To Arrange Protein Mmentioning
confidence: 89%
See 1 more Smart Citation
“…Their orientation is, however, important for proper interpretation of such experiments [Sekimoto and Tawada, 1995;Imafuku et al, 1996]. Long thick filaments of bivalve muscles were used to overcome this problem, and it was concluded that some cooperative coordination exists between many motors on thick filaments in the actomyosin system [Noda et al, 2005]. Similarly, the present experimental system can be used for the kinesinmicrotubule motility system.…”
Section: Discussion Catchin Filaments Are Useful To Arrange Protein Mmentioning
confidence: 89%
“…The images were recorded with a digital videocassette recorder (DSR-45, Sony, Tokyo, Japan). The images were then analyzed essentially as described previously [Imafuku et al, 1996;Noda et al, 2005]. In brief, the recorded images were transferred to a computer frame by frame, and the x and y coordinates of the leading end of the microtubules on each frame was digitized by using a mouse-driven cursor on the screen.…”
Section: Motility Assay and Data Analysesmentioning
confidence: 99%